Transcranial pulsed Doppler ultrasound findings in brain stem death. Issue 11 (November 1987) - Kirkham, F J; Levin, S D; Padayachee, T S; Kyme, M C; Neville, B G; Gosling, R G
Abstract : Data are presented from transcranial insonation of the middle cerebral artery (MCA) performed at intervals in 23 unconscious children for whom the outcome was subsequently poor. Once an MCA signal had been observed over a 30 minute period with time averaged velocity less than 10 cm s-1 and/or a direction of flow index, DFI, defined as 1 minus the ratio of reverse to forward flow of less than 0.8, recovery to forward flow throughout diastole was never observed and no patient recovered brain stem reflexes. Recovery of forward flow in diastole, and of brain stem function, was seen in cases with time averaged MCA velocity in the range 10 to 25 cm s-1 and with reverse flow but a DFI of greater than 0.8 for short periods of time. All but one of the 13 children fulfilling clinical criteria for brain stem death had MCA signals with time averaged velocity of less than 10 cm/s and DFI of less than 0.8. This type of signal was not observed in five children who were left in a persistent vegetative state.